2013
DOI: 10.4103/1687-4293.123793
|View full text |Cite
|
Sign up to set email alerts
|

Volatile oils, lipid constitutes and the antimicrobial activity of Daucus syrticus growing in Libya

Abstract: This work aims to investigate the volatile oils, lipid constitutes, and antimicrobial activity of Daucus syrticus (DS) extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The volatile oil of the D. syrticus herb collected during January revealed the presence of different classes of terpene and non terpene compounds, among which γ-terpinene, α-terpineol, α-humulene, α-bisabolol, neophytadiene, phytol, heptacosane, nonacosane, n-hexadecanoic acid, 9,12,15-octadecatrienoic acid methyl ester and acetyl-5-methyl-furan were found to be the main compounds, and the data obtained from the GLC analysis of the unsaponifiable fraction showed that, it contains a series of hydrocarbons (80.24%), sterols, (2.28% cholesterol, campasterol, stigmasterol, and β-sitosterol) and triterpenes (0.96% α-amyrine), while the GLC of fatty acid methyl esters revealed the presence of saturated fatty acids (35%) and unsaturated fatty acids (65%), among which plasmatic and linolenic acid are the main compounds, respectively (Abd Alla et al, 2013 andMansour et al, 2004).…”
Section: Gc/ms Of Volatile Oils Of D Syrticus Murbmentioning
confidence: 99%
“…The volatile oil of the D. syrticus herb collected during January revealed the presence of different classes of terpene and non terpene compounds, among which γ-terpinene, α-terpineol, α-humulene, α-bisabolol, neophytadiene, phytol, heptacosane, nonacosane, n-hexadecanoic acid, 9,12,15-octadecatrienoic acid methyl ester and acetyl-5-methyl-furan were found to be the main compounds, and the data obtained from the GLC analysis of the unsaponifiable fraction showed that, it contains a series of hydrocarbons (80.24%), sterols, (2.28% cholesterol, campasterol, stigmasterol, and β-sitosterol) and triterpenes (0.96% α-amyrine), while the GLC of fatty acid methyl esters revealed the presence of saturated fatty acids (35%) and unsaturated fatty acids (65%), among which plasmatic and linolenic acid are the main compounds, respectively (Abd Alla et al, 2013 andMansour et al, 2004).…”
Section: Gc/ms Of Volatile Oils Of D Syrticus Murbmentioning
confidence: 99%
“…Additionally, they play a role in enhancing vision, inducing apoptosis, providing neuroprotection, and influencing blood vessels and platelets, which may potentially reduce the risk of coronary heart disease [ 15 ]. Genus Daucus (Apiaceae) contains about 60 species distributed mainly in Africa, West Asia, and Europe, and a few species were found in Australia and North America [ 16 , 17 ]. It is represented in Libya by nine species, including D. durieua , D. muricatus , D. carota , D. guttatus , D. capillifolius , D. jordanicus , D. littorals , D. syrticus and D. sahariensis [ 18 ]…”
Section: Introductionmentioning
confidence: 99%